Structure of a dominant-negative helix-loop-helix transcriptional regulator suggests mechanisms of autoinhibition - Ishii, Ryohei (Nature Publishing Group, 2012)
Helix-loop-helix (HLH) family transcription factors regulate numerous developmental and homeostatic processes. Dominant-negative HLH (dnHLH) proteins lack DNA-binding ability and capture basic HLH (bHLH) transcription factors to inhibit cellular differentiation and enhance cell proliferation and motility, thus participating in patho-physiological processes. We report the first structure of a free-standing human dnHLH protein, HHM (Human homologue of murine maternal Id-like molecule). HHM adopts a V-shaped conformation, with N-terminal and C-terminal five-helix bundles connected by the HLH region. In striking contrast to the common HLH, the HLH region in HHM is extended, with its hydrophobic dimerization interfaces embedded in the N- and C-terminal helix bundles. Biochemical and physicochemical analyses revealed that HHM exists in slow equilibrium between this V-shaped form and the partially unfolded, relaxed form. The latter form is readily available for interactions with its target bHLH transcription factors. Mutations disrupting the interactions in the V-shaped form compromised the target transcription factor specificity and accelerated myogenic cell differentiation. Therefore, the V-shaped form of HHM may represent an autoinhibited state, and the dynamic conformational equilibrium may control the target specificity.